The effects of apostasy on the entitlement to property on death: the Malaysian position - Mohd Salim, Wan Noraini (IIUM Press, 2016)
Apostasy has always been a controversial issue in Malaysia. It inevitably leads to certain consequences and implications including the right of inheritance upon the death of a person. However, many do not have adequate knowledge on apostasy and its implications. This is especially seen among non-Muslims. Hence, misunderstanding and wrong perception towards Islam is further perpetuated. This article focuses on the implication of apostasy in the entitlement to property upon death both of a Muslim as well as an apostate. A discussion is also made on certain legal aspects of apostasy in Malaysia, which includes the problems of jurisdiction and administrative constraints in giving effect to the implication of apostasy in the entitlement to property upon death. The article analyses available literature on apostasy in Islam in the forms of textbooks, articles, seminar papers and decided cases. The main objective of the article is to address relevant contemporary issues on apostasy in Malaysia especially to its implications on entitlement to property upon death of either the apostate or his relative.